Development of a Web-Based Clothing Sales System for Efficiency and Customer Satisfaction - Andrian Hidayat; Dani Dani; A. Nurul Anwar (bit-Tech, 2026)
Advances in information technology have enabled businesses to increase operational efficiency and effectiveness. Web-based clothing sales information systems support improved sales processes and more accurate inventory management. The goal of this research is to create a web-based system for tracking garment sales statistics in order to increase efficiency and customer satisfaction. The waterfall system development process was employed in the Clothing Sales System research, which included the Customer Satisfaction phases of analysis, design, implementation, testing, and maintenance. The analysis stage identifies system requirements through observation, interviews, and questionnaires. The design phase focuses on system modeling with data flow diagrams and entity-relationship diagrams. The programming language used in the implementation stage is PHP, and the database is MySQL. To guarantee that the system works properly, the testing step uses both black-box and white-box approaches. The findings reveal that the built system performs effectively and satisfies user demands, with a 90% success rate. The system can increase sales by 20% and reduce operational costs by 15%, while improving inventory management and response times. In addition, the system contributes to customer satisfaction by providing more complete and accurate product information. The average customer satisfaction score was 4.25 out of 5, indicating high user satisfaction. The waterfall technique was used to create a web-based clothes sales information system that may significantly increase business efficiency and consumer happiness. This system also enhances operational performance and supports better decision-making in clothing sales management.